2014
DOI: 10.1111/cpf.12203
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Polar®RS800G3 heart rate monitor with Polar® S810i and electrocardiogram to obtain the series of RR intervals and analysis of heart rate variability at rest

Abstract: The Polar® RS800G3™ rate monitor was released in the market to replace the Polar® S810i™, and few studies have assessed that the RR series obtained by this equipment is reliable for analysis of heart rate variability (HRV). We compared HRV indexes among the devices Polar® RS800G3™, Polar® S810i™ and eletrocardiogram (ECG) to know whether the series of Polar® RS800G3™ are as reliable as those devices already validated. We analysed data from 30 healthy young adults, male, with an average age of 20·66 ± 1·40 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(73 citation statements)
references
References 13 publications
0
73
0
Order By: Relevance
“…The HRV analysis was registered during the whole experimental protocol by an HR receiver (Polar RS800CX, Finland), the equipment previously used to record the pulse rate of HR 16 . The HRV indices were determined at the following times: 10 th to 15 th minute of rest and during recovery (Rec): Rec1 (0 to 5 minutes), Rec2 (5 to 10 minutes), Rec3 (15 to 20 minutes), Rec4 (25–30 minutes), Rec5 (35 to 40 minutes), Rec6 (45 to 50 minutes) and Rec7 (55 to 60 minutes).…”
Section: Methodsmentioning
confidence: 99%
“…The HRV analysis was registered during the whole experimental protocol by an HR receiver (Polar RS800CX, Finland), the equipment previously used to record the pulse rate of HR 16 . The HRV indices were determined at the following times: 10 th to 15 th minute of rest and during recovery (Rec): Rec1 (0 to 5 minutes), Rec2 (5 to 10 minutes), Rec3 (15 to 20 minutes), Rec4 (25–30 minutes), Rec5 (35 to 40 minutes), Rec6 (45 to 50 minutes) and Rec7 (55 to 60 minutes).…”
Section: Methodsmentioning
confidence: 99%
“…These devices represent a convenient alternative to traditional electrocardiographs, as far as heart rate variability is concerned (Rezende Barbosa et al 2014;Quintana et al 2012). It is comprised of a transmitter worn around the chest and a receiver worn on the non-dominant wrist that stores the HR values.…”
Section: Differential Heart Ratementioning
confidence: 99%
“…Recently, their utilization in HRV-based studies (typically, in heart diagnostics) has also been reported (12,13,19,33). According to the results of comparison studies, top-level Polar watches (S810, S810i) can generally be considered as valid as traditional ECG in obtaining data for HR and HRV analysis (14,15,25,26,31,32,42,45), although limitations were also reported (25,45). In one study, however, the RS-800 system was found to be inferior compared to the traditional method (44).…”
Section: Discussionmentioning
confidence: 99%